The Experience Economy: Work Is Theater & Every Business a Stage - B. Joseph Pine II; James H. Gilmore (USA Harvard Business School Press, 1999)
Future economic growth lies in the value of experiences and transformations--good and services are no longer enough. We are on the threshold, say authors Pine and Gilmore, of the Experience Economy, a new economic era in which all businesses must orchestrate memorable events for their customers. The Experience Economy offers a creative, highly original, and yet eminently practical strategy for companies to script and stage the experiences that will transform the value of what they produce. From America Online to Walt Disney, the authors draw from a rich and varied mix of examples that showcase businesses in the midst of creating personal experiences for both consumers and businesses. The authors urge managers to look beyond traditional pricing factors like time and cost, and consider charging for the value of the transformation that an experience offers. Goods and services, say Pine and Gilmore, are no longer enough. Experiences and transformations are the basis for future economic growth, and The Experience Economy is the script from which managers can begin to direct their own transformations.
Keywords: Product management; Diversification in industry; Customer services; Business; Nonfiction; Economics; Entrepreneurship; Management; Communication; Sociology; Cultural; Design; HRM: Contemporary Issues (HRM2074-N ); Global Citizenship (BIN1064-N)